Response of Different Types of Chocolate to Impact Loading – Direct Impact - Kumbár Vojtěch; Trnka Jan; Votava Jiří; Šafránková Veronika; Dufková Renáta; Fajman Martin; Čupera Jiří; Nedomová Šárka; Hřivna Luděk; Buchar Jaroslav (Acta Technologica Agriculturae)
This study investigates the dynamic response of various chocolate types to direct impact at high strain rates, which has significant implications for practical applications such as production, packaging, and transportation. Five different chocolate types – extra dark, dark, milk, white, and ruby – were evaluated. Experiments were conducted using the Direct Impact Hopkinson Bar (DIHB) technique, which enables the study of the mechanical behaviour of materials at strain rates exceeding 103 s-1. The influence of specimen length on the mechanical response of the chocolates was also examined. Impact responses were characterized in both the time and frequency domains. Results indicate that dark chocolate exhibited the highest resistance to impact loading. Furthermore, an enhancement in mechanical properties with increasing impact velocity was observed across all chocolate types.